A synergistic antitumor effect of polyphyllin I and formosanin C on hepatocarcinoma cells. Issue 20 (15th October 2016) - Liu, Jing; Man, Shuli; Liu, Zhen; Ma, Long; Gao, Wenyuan
Graphical abstract: Abstract: Polyphyllin I (PPI) and formosanin C (FC) were regarded as effective and imperative components isolated from Rhizoma Paridis saponins (RPS) and exhibited strong anti-tumor effects on a variety of cancers. With the wide application of complex mixtures in clinics, synergistic interactions are of vital importance in phytomedicine. Therefore, it is of inherent importance to study whether there is a synergistic anti-tumor effect on PPI and FC from one herb. In this study, the viability was detected by MTT assay. The combination index (CI) analysis was used to assess their synergistic effect. Consequently, there was a synergistic anti-tumor effect between PPI and FC at a ratio of 1:1. The CI value was less than 1.0. Their combination significantly increased their single G1 phase arrest and mitochondria-dependent apoptotic pathway. Meanwhile, PPI and FC reduced the ability of cell migration. In conclusion, polyphyllin I and formosanin C showed a synergistic anti-tumor effect on hepatocarcinoma cells. The findings would provide the foundation for the use of RPS in the future.